ISLAM DI SPANYOL: Asal Usul dan Perkembangannya Desmaniar - Desmaniar Desmaniar (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
If trace the history of people's lives in the very oppressed Andalusians, the very cruel feudalism of the population, the taxes that are very burdensome, then with the presence of Islam is as a helper to those who are oppressed. Muslims come to uphold justice and truth. Moreover, in the presence of Islam, the turbulence of the religions that are there. The occurrence of oppositions between rulers, Islam came as a savior. So Islam in Andalus can last long because, when the presence of Islamic Europe is in a state of retreat, and Islam in a state of advanced and expansive. So Islam can survive for centuries in Andalus.